Awareness of Russian tourists traveling to tropical and equatorial countries about the prevention of infectious diseases during travel - N. N. Zverevа; E. Y. Pylaeva; A. A. Erovichenkov; M. A. Sayfullin; T. N. Elagina; V. A. Tovstik; R. F. Sayfullin; N. A. Antipyat; O. V. Shamsheva (LLC "Diagnostics and Vaccines", 2023)
Tropical countries have become increasingly popular destinations for Russian tourists in recent years, so this study is relevant for understanding the peculiarities of Russian travel. The purpose of the research is to analyze the awareness of Russian tourists traveling to tropical countries about the prevention of infectious diseases during travel. Materials and methods. A two-center cross-sectional study using a questionnaire was conducted from 2018 to 2021 on the basis of the Center for Medical Prevention and the Infectious Clinical Hospital No. 1). The analysis of 102 questionnaires of Russian travelers who traveled to tropical countries was carried out, the level of their awareness of the prevention of infectious diseases during travel, and adherence to vaccination were determined. Results. 102 adult travelers came to a doctor for vaccination, some of them planned to take children to a trip (24 children in total) from 2 to 18 years old. Most often, people aged 19-44 planned to go to tropical countries; there were no gender differences among travelers. Among the regions of departure of the respondents, the most common were East Africa, South America, West Africa, Latin America and the Caribbean. The most visited country was Tanzania. In the first place in terms of the purpose of travel was tourism, followed by business trips, visiting friends and relatives, education, and other purposes. In groups of travelers with and without children, there were no differences in the reasons for the trip, the organization of the trip, the duration of the trip, and accommodation during the trip. The main reasons for traveling were tourism, work, and visiting friends and relatives. The median duration of the trip was 15 days. Most often, travelers stayed at the hotel. Most travelers without children and all travelers with children planned to visit nature parks. Travelers' vaccination status and awareness of infectious diseases endemic in the country of departure were insufficient. Conclusion. The age and gender structure of travelers, the duration of trips, the main regions of departure, the place of residence during the trip, the purpose of the trip, the awareness of travelers about diseases in the region and ways to prevent them, about routine vaccination, and the commitment of travelers to vaccination and disease prevention were determined.